2006
DOI: 10.1113/jphysiol.2006.108753
|View full text |Cite
|
Sign up to set email alerts
|

The early effects of chronic hypoxia on the cardiovascular system in the rat: role of nitric oxide

Abstract: Experiments were performed under Saffan anaesthesia on normoxic (N) rats and on chronically hypoxic rats exposed to 12% O 2 for 1, 3 or 7 days (1, 3 or 7CH rats): N rats routinely breathed 21% O 2 and CH rats 12% O 2 . The 1, 3 and 7CH rats showed resting hyperventilation relative to N rats, but baseline heart rate (HR) was unchanged and arterial blood pressure (ABP) was lowered. Femoral vascular conductance (FVC) was increased in 1 and 3CH rats, but not 7CH rats. When 1-7CH rats were acutely switched to breat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
28
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 61 publications
(125 reference statements)
8
28
2
Order By: Relevance
“…It may also be due to decreased Ca 2ϩ sensitivity via hypoxia-mediated Rho kinase inactivation in SMCs (16,39). It has also been suggested that an increased NO or PG synthesis from the endothelium causes reduced contractions due to hypoxia (16,24,39,40); however, in the present study, the contractile responses were lower even in the presence of endothelial NO synthase and cyclooxygenase inhibitors. It is unlikely due to the decreased expression of agonist receptors, since a nonreceptor agonist KCl also showed reduced contractions.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…It may also be due to decreased Ca 2ϩ sensitivity via hypoxia-mediated Rho kinase inactivation in SMCs (16,39). It has also been suggested that an increased NO or PG synthesis from the endothelium causes reduced contractions due to hypoxia (16,24,39,40); however, in the present study, the contractile responses were lower even in the presence of endothelial NO synthase and cyclooxygenase inhibitors. It is unlikely due to the decreased expression of agonist receptors, since a nonreceptor agonist KCl also showed reduced contractions.…”
Section: Discussioncontrasting
confidence: 78%
“…To study various effects of hypoxia, humans, rabbits, and rats have been subjected to 12% O 2 for various times (hours or days) to decrease PO 2 by ϳ40% without any signs of distress or discomfort (11,17,24,35,40,43). We also exposed the rabbits to chronic/subacute hypoxia in a chamber with 12% O 2 for a maximum period of 5 days and did not see any signs of discomfort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such changes were suspected on the basis of the responses of the vessels to hypoxic demand. Indeed, several studies have demonstrated the influence of hypoxic stimulus on vessel diameters, which induces vasodilatation and congestion related to the liberation of many hypoxic mediators [6]. The release of these numerous substances, particularly nitric oxide (NO), induces significant vasodilatation and the discharge of inflammatory mediators, including vascular endothelial growth factor (VEGF), which is considered to be the main stimulus for the development of neovascularization.…”
Section: Introductionmentioning
confidence: 99%